Production method of PET optical base film for fire-retardant and toughened backboard module

CN122917367APending Publication Date: 2026-10-16NINGBO YINGRUI POLYMERIZATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510425090.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

PET属于线性热塑性高聚物,极限氧指数仅为21%左右遇火后极易发生燃烧,引发火灾;PET的玻璃化转变温度较高,在作为工程塑料使用时存在结晶速度慢、模塑和成型周 期较长、缺口冲击敏感、成型制品收缩率大、尺寸稳定性差等缺点,限制了它的广泛应用,因此有必要对其进行增韧改性

Benefits of technology

外表层添加了离子液功能化氮化硼纳米片,能够实现更好的降热阻燃,氮化硼纳米片的物理阻隔和 离子液体催化成炭作用,聚磷酸铵的加入进一步促进 PET 脱水炭化产生连续致密的膨胀炭层,同时产生氨气,实现气相和凝聚相的协同阻燃;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917367A_ABST
    Figure CN122917367A_ABST
Patent Text Reader

Abstract

The application discloses a production method of a flame-retardant and toughened PET optical base film for a backboard module, and the base film comprises a transparent anti-adhesion coating layer, an outer surface layer, a middle core layer and an inner surface layer; the outer surface layer is composed of PET, ionic liquid functionalized boron nitride nanosheets and ammonium polyphosphate; the middle core layer is composed of PET, TPAE, PMDA, graphene and carboxylated multi-walled carbon nanotubes; and the inner surface layer is composed of m-PET, silicon dioxide, composite wax, POE and PP-g-MAH. The PET optical base film prepared by the method has good toughening effect and excellent flame-retardant performance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical film technology, specifically a method for producing a PET optical base film for flame-retardant and toughened backplate modules. Background Technology

[0002] In the field of backplane modules, PET optical base film is a key material, and its performance directly affects the overall quality and application effect of the backplane module. With continuous technological advancements and rapid industry development, the performance requirements for PET optical base film used in backplane modules are increasingly stringent. It not only needs excellent optical properties but also outstanding performance in flame retardancy and toughening to meet the demands of complex and ever-changing application scenarios. PET is a linear thermoplastic polymer with a limiting oxygen index of only about 21%, making it highly flammable and prone to fire. PET also has a high glass transition temperature, which, when used as an engineering plastic, results in slow crystallization, long molding and forming cycles, sensitivity to notched impact, large shrinkage of molded products, and poor dimensional stability, limiting its widespread application. Therefore, toughening modification is necessary. Summary of the Invention

[0003] In view of the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a method for producing a PET optical base film for flame-retardant and toughened backplate modules.

[0004] To solve the above problems, the technical solution of the present invention is: a method for producing a PET optical base film for flame-retardant and toughened backplate modules, wherein the base film includes a transparent anti-stick coating, an outer outer layer, an intermediate core layer and an inner surface layer; The outer layer is composed of PET, ion-functionalized boron nitride nanosheets, and ammonium polyphosphate; The intermediate core layer is composed of PET, TPAE, PMDA, graphene, and carboxylated multi-walled carbon nanotubes; The inner surface layer is composed of m-PET, silica, composite wax, POE, and PP-g-MAH; The production method includes the following steps: (1) Using hexagonal boron nitride and ionic liquid as raw materials, ionic liquid functionalized boron nitride nanosheets were synthesized by in-situ exfoliation functionalization technology; (2) Weigh the raw materials according to the proportions of each component in the outer layer, middle core layer and inner surface layer; (3) The raw materials for the outer layer, the middle core layer and the inner surface layer are blended separately and sent to their respective extruders for mixing and plasticizing; (4) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (5) Use an air knife to attach the sheet to the cooling roller and cool it rapidly to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (6) The cast sheet is stretched to form a thin film; (7) Using trifluoropropyltrimethylcyclotrisiloxane, octamethylcyclotetrasiloxane and tetramethyldihydrodisiloxane as raw materials, an organic-inorganic hybrid modified fluorosilicone resin was prepared by ring-opening polycondensation, hydrosilylation and hydrolysis co-condensation reaction. The resin was then coated onto the outer surface of a thin film to obtain a transparent non-stick coating.

[0005] (8) Wind up the film.

[0006] Further, step (1) specifically involves: placing hexagonal boron nitride powder into a ceramic crucible, heating it to 1000°C in a muffle furnace and maintaining it for 4 hours, and then allowing the hexagonal boron nitride nanosheets to cool naturally to room temperature to obtain oxidized boron nitride solid powder. The boron nitride solid powder is then added to a mixture of deionized water and ionic liquid, ultrasonically treated for 8 hours, centrifuged at 8000 rpm for 15 minutes, the precipitate is collected, and vacuum dried at 60°C to obtain ionic liquid functionalized boron nitride nanosheets.

[0007] Furthermore, step (7) includes the following steps: (71) Trifluoropropyltrimethylcyclotrisiloxane and octamethylcyclotetrasiloxane were added to a container equipped with a stirrer, thermometer and reflux condenser. The mixture was stirred until it was evenly heated. When the system was heated to 45°C, concentrated sulfuric acid catalyst was added and the reaction was kept at a constant temperature for 1 hour. Then, tetramethyldihydrodisiloxane, the end-capping agent, was added and the reaction was kept at a constant temperature for 5 hours. After that, anhydrous sodium carbonate was used to neutralize the concentrated sulfuric acid in the system. The mixture was filtered and the low-boiling substances were removed by vacuum distillation. The resulting colorless, transparent, low-viscosity oily liquid was the fluorinated and hydrogen-containing silicone oil. (72) Fluorine-containing hydrogen-containing silicone oil and vinyltriethoxysilane were added to a container equipped with a stirrer, thermometer and reflux condenser at a molar ratio of 1.1:1. The mixture was stirred evenly. After the system was heated to 90°C and stirred for 20 min, chloroplatinic acid catalyst was added and the reaction was continued at a constant temperature for 4 h to obtain a colorless, transparent and slightly viscous oily liquid, which is the intermediate of alkoxy-modified fluorine-containing polysiloxane. (73) The alkoxy-modified fluorinated polysiloxane intermediate, tetraethyl orthosilicate, and octyltriethoxysilane were added to a container containing anhydrous ethanol in a molar ratio of 6:4:3. The mixture was stirred evenly. When the system was heated to 60°C, hydrochloric acid was added to adjust the pH of the system to 3.5. After reacting for 30 min, distilled water was slowly added dropwise. The mixture was hydrolyzed and polycondensed for 5.5 h to obtain an organic-inorganic hybrid modified fluorosilicone resin. The organic-inorganic hybrid modified fluorosilicone resin was diluted with n-heptane to a solid content of 20%. It was then coated onto the outer surface of a film using a 10 μm coater to obtain a transparent non-stick coating.

[0008] Furthermore, the components of the outer layer are as follows by mass ratio: PET 97%, ion-functionalized boron nitride nanosheets 2%, and ammonium polyphosphate 1%.

[0009] Furthermore, the components of the intermediate core layer are as follows by mass ratio: PET 79.45%, TPAE 20%, PMDA 0.5%, graphene 0.02%, and carboxylated multi-walled carbon nanotubes 0.03%.

[0010] Furthermore, the components of the inner surface layer are as follows by mass ratio: m-PET 79.2%, silica 5%, composite wax 5%, POE 9%, and PP-g-MAH 1.8%.

[0011] The beneficial effects of this invention are: The outer layer is enhanced with ionic liquid-functionalized boron nitride nanosheets, which can achieve better heat reduction and flame retardancy. The physical barrier of boron nitride nanosheets and the catalytic char formation of ionic liquid, along with the addition of ammonium polyphosphate, further promote the dehydration and carbonization of PET to produce a continuous and dense expanded carbon layer, while generating ammonia gas, thus achieving synergistic flame retardancy of the gas phase and condensed phase. The addition of TPAE to the middle core layer can enhance toughness, giving the composite material stronger impact resistance and better durability. Pyromellitic dianhydride is used to improve the melt viscosity and strength of the system, thereby improving processing performance and the mechanical properties of the product. The addition of graphene and carboxylated multi-walled carbon nanotubes to the middle core layer can effectively improve the mechanical properties of the composite material. The inner surface layer m-PET is chain-extended polyethylene terephthalate. Compared with pure PET, m-PET has improved tensile strength and notched impact strength. After adding POE and PP-g-MAH, the elongation at break and notched impact strength are also improved. The inner surface layer is enriched with silica and composite wax. Silica, as an inorganic anti-blocking agent, enables the material to form a stable anti-blocking effect, while the composite wax can form a slip gradient in the material, effectively reducing the coefficient of friction. The two can significantly reduce the coefficient of friction of PET sheets, exhibiting excellent sliding performance. Transparent non-stick coatings can improve the transparency of films and enhance their hydrophobicity. Attached Figure Description

[0012] Figure 1 This is a schematic diagram of the structure of the optical base film of the present invention.

[0013] As shown in the figure: 1—transparent non-stick coating, 2—outer layer, 3—intermediate core layer, 4—inner surface layer. Detailed Implementation

[0014] To provide a more intuitive and complete understanding of the technical solution of this invention, the following non-limiting features are described in conjunction with the accompanying drawings: like Figure 1As shown, a method for producing a PET optical base film for a flame-retardant and toughened back panel module is provided. The base film includes a transparent anti-stick coating 1, an outer outer layer 2, an intermediate core layer 3, and an inner surface layer 4. The outermost layer 2 is composed of PET, ion-functionalized boron nitride nanosheets, and ammonium polyphosphate; The intermediate core layer 3 is composed of PET, TPAE, PMDA, graphene, and carboxylated multi-walled carbon nanotubes; The inner surface layer 4 is composed of m-PET, silica, composite wax, POE, and PP-g-MAH; The production method of PET optical base film for flame-retardant and toughened backplate modules includes the following steps: (1) Using hexagonal boron nitride and ionic liquid as raw materials, ionic liquid functionalized boron nitride nanosheets were synthesized by in-situ exfoliation functionalization technology; (2) Weigh the raw materials according to the proportions of each component in the outer layer, middle core layer and inner surface layer; (3) The raw materials for the outer layer, the middle core layer and the inner surface layer are blended separately and sent to their respective extruders for mixing and plasticizing; (4) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (5) Use an air knife to attach the sheet to the cooling roller and cool it rapidly to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (6) The cast sheet is stretched to form a thin film; (7) Using trifluoropropyltrimethylcyclotrisiloxane, octamethylcyclotetrasiloxane and tetramethyldihydrodisiloxane as raw materials, an organic-inorganic hybrid modified fluorosilicone resin was prepared by ring-opening polycondensation, hydrosilylation and hydrolysis co-condensation reaction. The resin was then coated onto the outer surface of a thin film to obtain a transparent non-stick coating.

[0015] (8) Wind up the film.

[0016] Step (1) is as follows: Hexagonal boron nitride powder is placed in a ceramic crucible and heated to 1000℃ in a muffle furnace and kept for 4 hours. After the hexagonal boron nitride nanosheets are naturally cooled to room temperature, oxidized boron nitride solid powder is obtained. The boron nitride solid powder is added to a mixture of deionized water and ionic liquid, ultrasonically treated for 8 hours, centrifuged at 8000 rpm for 15 minutes, the precipitate is taken, and vacuum dried at 60℃ to obtain ionic liquid functionalized boron nitride nanosheets.

[0017] Step (7) includes the following steps: (71) Trifluoropropyltrimethylcyclotrisiloxane and octamethylcyclotetrasiloxane were added to a container equipped with a stirrer, thermometer and reflux condenser. The mixture was stirred until it was evenly heated. When the system was heated to 45°C, concentrated sulfuric acid catalyst was added and the reaction was kept at a constant temperature for 1 hour. Then, tetramethyldihydrodisiloxane, the end-capping agent, was added and the reaction was kept at a constant temperature for 5 hours. After that, anhydrous sodium carbonate was used to neutralize the concentrated sulfuric acid in the system. The mixture was filtered and the low-boiling substances were removed by vacuum distillation. The resulting colorless, transparent, low-viscosity oily liquid was the fluorinated and hydrogen-containing silicone oil. (72) Fluorine-containing hydrogen-containing silicone oil and vinyltriethoxysilane were added to a container equipped with a stirrer, thermometer and reflux condenser at a molar ratio of 1.1:1. The mixture was stirred evenly. After the system was heated to 90°C and stirred for 20 min, chloroplatinic acid catalyst was added and the reaction was continued at a constant temperature for 4 h to obtain a colorless, transparent and slightly viscous oily liquid, which is the intermediate of alkoxy-modified fluorine-containing polysiloxane. (73) The alkoxy-modified fluorinated polysiloxane intermediate, tetraethyl orthosilicate, and octyltriethoxysilane were added to a container containing anhydrous ethanol in a molar ratio of 6:4:3. The mixture was stirred evenly. When the system was heated to 60°C, hydrochloric acid was added to adjust the pH of the system to 3.5. After reacting for 30 min, distilled water was slowly added dropwise. The mixture was hydrolyzed and polycondensed for 5.5 h to obtain an organic-inorganic hybrid modified fluorosilicone resin. The organic-inorganic hybrid modified fluorosilicone resin was diluted with n-heptane to a solid content of 20%. It was then coated onto the outer surface of a film using a 10 μm coater to obtain a transparent non-stick coating.

[0018] The components of the outer layer, the middle core layer, and the inner surface layer are in the following mass ratio: outer layer 20%, middle core layer 60%, and inner surface layer 20%.

[0019] The outer layer consists of the following components by mass ratio: PET 97%, ion-functionalized boron nitride nanosheets 2%, and ammonium polyphosphate 1%.

[0020] The components of the intermediate core layer, by mass ratio, are: PET 79.45%, TPAE 20%, PMDA 0.5%, graphene 0.02%, and carboxylated multi-walled carbon nanotubes 0.03%. The graphene is submicron-sized graphene oxide.

[0021] The components of the inner surface layer, by mass ratio, are: m-PET 79.2%, silica 5%, composite wax 5%, POE 9%, and PP-g-MAH 1.8%. The composite wax is composed of natural paraffin wax, synthetic wax, and carnauba wax.

[0022] The preparation method of m-PET is as follows: after PET is dried, it is mixed with triglycidyl isocyanurate, hexamethylene diisocyanate and antioxidant 1010. After the mixture is evenly mixed, it is reacted and extruded in a twin-screw extruder and then cut and granulated to obtain m-PET.

[0023] This invention incorporates ionic liquid-functionalized boron nitride nanosheets into the outer layer, achieving enhanced heat reduction and flame retardancy. The physical barrier effect of the boron nitride nanosheets and the catalytic char formation by the ionic liquid, along with the addition of ammonium polyphosphate, further promote the dehydration and carbonization of PET, generating a continuous and dense expanded char layer while simultaneously producing ammonia gas, thus achieving synergistic flame retardancy in both the gas and condensed phases. Boron nitride nanosheets, a two-dimensional layered structure material, possess excellent electrical insulation and high thermal conductivity. As a flame retardant or flame retardant synergist, boron nitride nanosheets act as a barrier, inhibiting heat from reaching the polymer matrix and achieving effective flame retardancy. Ionic liquids are novel green solvents with high thermal stability and good solubility, exhibiting excellent flame retardant properties. The nanosheet barrier effect of boron nitride nanosheets and the ionic liquid, as a good charring agent, promote the early decomposition of PET to form a protective char layer. Their synergistic effect slows down the combustion reaction. Ammonium polyphosphate decomposes upon heating to generate phosphorus free radicals, which can effectively capture free radicals generated during combustion, while simultaneously generating non-flammable ammonia gas, promoting gas-phase flame retardancy.

[0024] The addition of TPAE to the core layer provides a toughening effect, resulting in a composite material with enhanced impact resistance and improved durability. Pyromellitic dianhydride is used to increase the melt viscosity and strength of the system, improving processing performance and the mechanical properties of the product. TPAE, known for its low density and high strength, exhibits excellent flexibility and durability in use. Its high resilience and impact resistance allow it to quickly recover its original shape after impact, maintaining its flexibility and elasticity even at low temperatures. The interfacial bonding between TPAE and PET is a key aspect of material toughening. Upon impact, this interfacial bonding ensures a tight bond between TPAE particles and PET, allowing them to jointly absorb impact energy. This tight bond helps disperse and dissipate impact energy, enhancing the overall toughness of the material. Pyromellitic dianhydride, as an effective chain extender, contains four reactive sites that can react with TPAE or PET. The end groups of the molecular chain (such as terminal hydroxyl or terminal carboxyl groups) undergo chemical reactions, thereby extending the molecular chain and achieving the purpose of chain extension and thickening. This chain extension effect can increase the length and branching degree of the polymer molecular chain, improve the melt viscosity and strength of the system, and thus improve the processing performance and mechanical properties of the final product.

[0025] The addition of graphene and carboxylated multi-walled carbon nanotubes to the middle core layer can effectively improve the mechanical properties of the composite material. The graphene / carboxylated multi-walled carbon nanotube hybrid material is embedded in the PET matrix and has good compatibility with the PET matrix, thereby promoting the improvement of its mechanical strength.

[0026] The inner surface layer m-PET is chain-extended polyethylene terephthalate. Compared with pure PET, m-PET has improved tensile strength and notched impact strength. After adding POE and PP-g-MAH, the elongation at break and notched impact strength are also improved. As the chain-extended PET is modified, the intermolecular forces increase, thus improving tensile strength and impact strength. When the material is impacted, the elastomer POE dispersed inside absorbs the impact energy, improving the material's impact resistance. Adding an appropriate amount of compatibilizer PP-g-MAH can improve the compatibility between PET and POE, thereby improving mechanical properties.

[0027] The inner surface layer is enriched with silica and composite wax. Silica, as an inorganic anti-blocking agent, enables the material to form a stable anti-blocking effect, while the composite wax can form a slip gradient in the material, effectively reducing the coefficient of friction. The two can significantly reduce the coefficient of friction of PET sheets, exhibiting excellent sliding performance. Silica has a refractive index similar to PET, and the composite wax is formulated with fatty acid esters of different alkyl chain lengths. Several waxes with different melting points can form a slip gradient, thereby effectively reducing the coefficient of friction of the sheet.

[0028] Transparent anti-stick coatings can improve the transparency and hydrophobicity of films. These coatings exhibit significant hydrophobicity, containing papillary structures of varying sizes. This is because organic fluorine is highly polar, possessing strong hydrophobic and oleophobic properties, but exhibits only moderate wettability with the base film and poor compatibility with other organic phases. In contrast, inorganic nanoparticles tend to aggregate during thermal curing, forming aggregates of inorganic hybrid particles encapsulated by organic C-F bonds. This causes coating shrinkage and the formation of papillary structures. This unique structure endows the coating surface with excellent anti-stick properties. Due to their strong polarity, fluorine-containing groups spontaneously migrate to the coating surface upon heating. The inorganic-organic co-modification reduces the surface energy of the coating, improving its hydrophobicity. Furthermore, the introduction of organic-inorganic hybrid particles into the coating reduces the light reflection flux and increases the transmitted light flux, thereby increasing light transmittance.

Claims

1. A method for producing a PET optical base film for a flame-retardant and toughened backplate module, characterized in that: The base film includes a transparent anti-stick coating, an outer outer layer, an intermediate core layer, and an inner outer layer; The outer layer is composed of PET, ion-functionalized boron nitride nanosheets, and ammonium polyphosphate; The intermediate core layer is composed of PET, TPAE, PMDA, graphene, and carboxylated multi-walled carbon nanotubes; The inner surface layer is composed of m-PET, silica, composite wax, POE, and PP-g-MAH; The production method includes the following steps: (1) Using hexagonal boron nitride and ionic liquid as raw materials, ionic liquid functionalized boron nitride nanosheets were synthesized by in-situ exfoliation functionalization technology; (2) Weigh the raw materials according to the proportions of each component in the outer layer, middle core layer and inner surface layer; (3) The raw materials for the outer layer, the middle core layer and the inner surface layer are blended separately and sent to their respective extruders for mixing and plasticizing; (4) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (5) Use an air knife to attach the sheet to the cooling roller and cool it rapidly to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (6) The cast sheet is stretched to form a thin film; (7) Using trifluoropropyltrimethylcyclotrisiloxane, octamethylcyclotetrasiloxane and tetramethyldihydrodisiloxane as raw materials, an organic-inorganic hybrid modified fluorosilicone resin was prepared by ring-opening polycondensation, hydrosilylation and hydrolysis co-condensation reaction. The resin was then coated on the outer surface of a film to obtain a transparent non-stick coating. (8) Wind up the film.

2. The method for producing a flame-retardant and toughened PET optical base film for a backplate module according to claim 1, characterized in that: Step (1) is as follows: Hexagonal boron nitride powder is placed in a ceramic crucible and heated to 1000℃ in a muffle furnace and kept for 4 hours. After the hexagonal boron nitride nanosheets are naturally cooled to room temperature, oxidized boron nitride solid powder is obtained. The boron nitride solid powder is added to a mixture of deionized water and ionic liquid, ultrasonically treated for 8 hours, centrifuged at 8000 rpm for 15 minutes, the precipitate is taken, and vacuum dried at 60℃ to obtain ionic liquid functionalized boron nitride nanosheets.

3. The method for producing a PET optical base film for a flame-retardant and toughened backplate module according to claim 1, characterized in that: Step (7) includes the following steps: (71) Trifluoropropyltrimethylcyclotrisiloxane and octamethylcyclotetrasiloxane were added to a container equipped with a stirrer, thermometer and reflux condenser. The mixture was stirred until it was evenly heated. When the system was heated to 45°C, concentrated sulfuric acid catalyst was added and the reaction was kept at a constant temperature for 1 hour. Then, tetramethyldihydrodisiloxane, the end-capping agent, was added and the reaction was kept at a constant temperature for 5 hours. After that, anhydrous sodium carbonate was used to neutralize the concentrated sulfuric acid in the system. The mixture was filtered and the low-boiling substances were removed by vacuum distillation. The resulting colorless, transparent, low-viscosity oily liquid was the fluorinated and hydrogen-containing silicone oil. (72) Fluorine-containing hydrogen-containing silicone oil and vinyltriethoxysilane were added to a container equipped with a stirrer, thermometer and reflux condenser at a molar ratio of 1.1:

1. The mixture was stirred evenly. After the system was heated to 90°C and stirred for 20 min, chloroplatinic acid catalyst was added and the reaction was continued at a constant temperature for 4 h to obtain a colorless, transparent and slightly viscous oily liquid, which is the intermediate of alkoxy-modified fluorine-containing polysiloxane. (73) The alkoxy-modified fluorinated polysiloxane intermediate, tetraethyl orthosilicate, and octyltriethoxysilane were added to a container containing anhydrous ethanol in a molar ratio of 6:4:

3. The mixture was stirred evenly. When the system was heated to 60°C, hydrochloric acid was added to adjust the pH of the system to 3.

5. After reacting for 30 min, distilled water was slowly added dropwise. The mixture was hydrolyzed and polycondensed for 5.5 h to obtain an organic-inorganic hybrid modified fluorosilicone resin. The organic-inorganic hybrid modified fluorosilicone resin was diluted with n-heptane to a solid content of 20%. It was then coated onto the outer surface of a film using a 10 μm coater to obtain a transparent non-stick coating.

4. A method for producing a flame-retardant and toughened PET optical base film for a backplate module according to claim 1, characterized in that: The outer layer consists of the following components by mass ratio: PET 97%, ion-functionalized boron nitride nanosheets 2%, and ammonium polyphosphate 1%.

5. A method for producing a flame-retardant and toughened PET optical base film for a backplate module according to claim 1, characterized in that: The components of the intermediate core layer by mass ratio are: PET 79.45%, TPAE 20%, PMDA 0.5%, graphene 0.02%, and carboxylated multi-walled carbon nanotubes 0.03%.

6. A method for producing a flame-retardant and toughened PET optical base film for a backplate module according to claim 1, characterized in that: The components of the inner surface layer by mass ratio are: m-PET 79.2%, silica 5%, composite wax 5%, POE 9%, PP-g-MAH 1.8%.